Regional Disparities and Divergent Trends in Geriatric Headache, Neck Pain, and Low Back Pain Across Asia–Europe Regions Related to the Belt and Road Corridor. - Liu, Jiye; Lei, Jiawei; Liang, Qiqi; Sun, Weimin; Li, Jiachun; Wang, Haoran; Shen, Ao; Huang, Jianhua; Wang, Jiahe; Liu, Xin (Inquiry (00469580), 2026)
Introduction: Pain is a common geriatric syndrome that substantially affects the quality of life of older adults and imposes substantial socioeconomic burdens. This study systematically analyzes the disease burden of geriatric headache, neck pain, and low back pain, including their changing trends, among people aged 60 years and older in core geographic regions in Asia and Europe related to the Belt and Road corridor, which include East Asia, Southeast Asia, South Asia, Central Asia, the Middle East and North Africa, and Central and Eastern Europe. Methods: For the period 1990–2023, this population-based secondary analysis covered the same core geographic regions in Asia and Europe related to the Belt and Road corridor as described in the Introduction. Data from the Global Burden of Disease (GBD) 2023 study were used to extract incidence rates, prevalence rates, and years lived with disability (YLDs) for the aforementioned pain symptoms from 1990 to 2023. Age-standardized rates (ASRs) were calculated and compared. Percentage change analysis, gender- and age-stratified analyses, social demographic index (SDI) correlation analysis, the concentration index of inequality (CII), and frontier efficiency analysis were applied to comprehensively evaluate regional differences in disease burden and their influencing factors. Results: In 2023, the age-standardized incidence rate (ASIR) of headache was highest in Eastern Europe (12290.45/100000) and lowest in East Asia (7746.20/100000). The age-standardized incidence rate of low back pain was highest in Central Europe (5129.76/100000) and lowest in South Asia (2902.60/100000). The age-standardized incidence rate of neck pain was highest in the Middle East and North Africa (707.06/100000) and lowest in South Asia (362.33/100000). Between 1990 and 2023, divergent trends were observed: the burden of low back pain in East Asia declined significantly, with decreases of 23.37% in age-standardized incidence rate (ASIR) and 24.39% in age-standardized YLD rate (ASYR), whereas the burden of headache increased significantly, with increases of 5.68% in ASIR and 6.86% in ASYR. Across all regions, women experienced a higher pain burden than men, with the most pronounced sex differences observed in the Middle East and North Africa. SDI was significantly positively correlated with the burden of low back pain but showed no significant correlation with headache or neck pain. Health inequality analysis indicated that the burden of headache tended to be concentrated among lower-income populations, whereas the burden of low back pain was concentrated among higher-income populations. Frontier efficiency analysis revealed substantial potential for improvement in pain management in countries in the Middle East, North Africa, and Eastern Europe. Conclusion: Marked regional disparities exist in the pain burden among older adults along the "Belt and Road," which may be associated with the combined effects of population aging, stages of socioeconomic development, cultural factors, and health system efficiency. These findings could inform the development of regionally targeted pain prevention and might support strengthening cooperation in healthy aging. Future efforts should integrate local realities and promote cross-departmental and cross-regional interventions to reduce the pain burden among older adults and improve their quality of life. All estimates are derived from GBD modeled outputs, not primary observed data.